The effect of product innovation and service quality on customer loyalty is mediated by customer satisfaction at PT KB Finansia Multifinance (Kredit plus) Tasikmalaya - Agus Yuna Syariful; Saparso; Rudolf Lumbantobing (Enrichment : Journal of Management, 2023)
Business competition in the field of non-bank financing services (multifinance) in Indonesia is increasing. The increasing economic and lifestyle needs of the Indonesian people have made businesses in this field grow and develop rapidly, the fintech market is already large, especially in Java, which is the largest market for traditional financial companies. The purpose of this study was to determine the effect of product innovation and service quality on customer loyalty mediated by customer satisfaction. The population in this study were all employees of PT KB Finansia Multifinance and were processed using Structural Equation Model (SEM) analysis with SEM PLS software. Based on the results of the study, empirical facts were obtained in the form of 1) There was a significant positive effect on product innovation variables on customer satisfaction 2) There is no positive influence of service quality variables on customer satisfaction 3) There is a significant positive effect on product innovation variables on Customer Loyalty 4) There is a significant positive effect of service quality variables on customer loyalty 5) There is no positive influence of customer satisfaction on customer loyalty 6) Customer satisfaction does not significantly mediate the positive effect of product innovation on customer loyalty 7) Customer satisfaction does not significantly mediate the positive effect of service quality on customer loyalty.